2019
DOI: 10.1155/2019/1948123
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lightly Burnt MgO Expansive Agent on the Deformation and Microstructure of Reinforced Concrete Wall

Abstract: Compensation for shrinkages with three kinds of lightly burnt MgO expansive agent (LBMEA) is used in a reinforced concrete wall poured in the summer. Influences of the internal temperature history on the expansion of concrete and the microstructure of cement paste containing LBMEA were investigated. The results showed that LBMEA exhibited significant expansion around the end of the fall temperature stage; then, the expansion rate declined obviously, and concrete containing LBMEA with low hydration reactivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…According to Chinese standard GB/T 50081-2019 [ 42 ], the concrete was poured into molds whose dimensions were 150 mm × 150 mm × 150 mm. Cured in the variable temperature oven for 24 h, concrete specimens would be removed from molds and wrapped in plastic wrap, after which they continued to be cured.…”
Section: Methodsmentioning
confidence: 99%
“…According to Chinese standard GB/T 50081-2019 [ 42 ], the concrete was poured into molds whose dimensions were 150 mm × 150 mm × 150 mm. Cured in the variable temperature oven for 24 h, concrete specimens would be removed from molds and wrapped in plastic wrap, after which they continued to be cured.…”
Section: Methodsmentioning
confidence: 99%
“…She found that the hydration reaction of light-burned MgO is consistent with the first-order reaction kinetics; that is, the hydration process is controlled by chemical reactions. Jiaping Liu [23] and Changwen Miao [24] found that the effect of increasing temperature on hydration of high activity magnesium oxide expansion agent is more significant. The expansion of high activity magnesium oxide expansion agent at normal temperature is lower than that of low activity magnesium oxide expansion agent, but higher than that of the low activity magnesium oxide expansion agent at high temperature.…”
Section: Introductionmentioning
confidence: 99%